The Effect of Self Esteem and Learning Motivation on Learning Achievement Mediated by Emotional Intelligence - Nilawati, Raden Roro Baiduri; Ghufron, Muhammad; Nurani, Diah Kukuh (Devotion : Journal of Research and Community Service, 2024)
This study aims to investigate the effect of self esteem and learning motivation on learning achievement with the mediator of emotional intelligence in students at SMAN 39 Jakarta. The sample of this study consisted of students at SMAN 39 Jakarta. Data were collected through questionnaires that measured the level of self esteem, learning motivation, emotional intelligence, and learning achievement. Data analysis was conducted using path analysis method with mediation approach. The results showed that there is a relationship between Self Esteem has a positive effect of 0.23 and a significant t value = 2.27 on Learning Achievement. Learning motivation has a positive effect of 0.27 and a significant t value = 4.51 on Emotional Intelligence. Emotional Intelligence has a negative effect of -0.22 and a value of t = -2.10 which means significant to Learning Achievement. Self Esteem has more influence on Emotional Intelligence than Learning Achievement, Learning motivation has more influence on Learning Achievement than Emotional Intelligence. The results of this study provide further understanding of the factors that influence student achievement, as well as the importance of the role of emotional intelligence as a mediator in the relationship between self esteem and learning motivation with learning achievement. This research has important implications in the context of education, especially in efforts to improve student achievement. The results of this study can be used as a basis for developing programs and interventions that aim to improve students' self esteem, learning motivation, and emotional intelligence.